Hubungan antara Umur, Tingkat Pendidikan dan Perilaku Petani dalam Penggunaan Pestisida (Studi Kasus di Kelurahan Jogomerto Kec. Tanjunganom Kab. Nganjuk tahun 2017) - Miftachul Jannah; Koerniasari .; Bambang Sunarko (GEMA LINGKUNGAN KESEHATAN, 2018)
line" Farmer’s behavior, level of education, and ages which are low is the factor that causes the usage of pesticide is out of the guidelines by the farmers nowadays. Using pesticide without following the guidelines will cause negative impact for the farmers their selves especially in health aspect. The research was purposed to find out the relationship between ages, level of education, and farmer’s behavior in using pesticide by interviewing and observing the farmers while working and using the pesticide. Based on the characteristic, this is an observational research with cross sectional approaching. Interviews and observation are the method that is used to collect the data. 86 populations of farmers and 71 sampling are selected to participate in the research. Then the data will be analyzed by trial chi-square technique in a computer. The result showed 46.5% productive farmers is about 16 to 64 years-old and 32.5% farmers have good enough behavior that used pesticide out of the guidelines, significantly affects (p0.05), and does not affect (p0.05) that is the level of education. That is why the writer recommends next movement in order to follow the guidelines of using pesticide by giving socialization to the farmers and adding their education of how to use pesticide properly. The governments need to give counseling and socialization routinely for the farmers in order to avoid the danger of pesticide just like poisoning. Reading List : 22 pieces (1990-2016) Classification : - Keywords : farmers’ individual factor, pesticide usage